Early ankle movement versus immobilization in the postoperative management of ankle fracture in adults: a systematic review and meta-analysis. - Keene, D; Williamson, E; Bruce, J; Willett, K; Lamb, S (2014)
STUDY DESIGN: Systematic review and meta-analysis. OBJECTIVES: To compare early ankle movement versus ankle immobilization after surgery for ankle fracture on clinical and patient-reported outcomes. BACKGROUND: A significant proportion of patients undergoing surgery for ankle fracture experience postoperative complications and delayed return to function. The risks and benefits of movement of the ankle in the first 6 weeks after surgery are not known, and clinical practice varies widely. METHODS: We searched bibliographic databases and reference lists to identify eligible trials. Two independent reviewers conducted data extraction and risk-of-bias assessments. RESULTS: Fourteen trials (705 participants) were included in the review, 11 of which were included in the meta-analysis. The quality of the trials was universally poor. The pooled effect of early ankle movement on function at 9 to 12 weeks after surgery compared to immobilization was inconclusive (standardized mean difference, 0.46; 95% confidence interval: -0.02, 0.93; P = .06; I(2) = 72%), and no differences were observed between groups at 1 year. The odds of venous thromboembolism were significantly lower with early ankle movement compared to immobilization (Peto odds ratio = 0.12; 95% confidence interval: 0.02, 0.71; P = .02; I(2) = 0%). Deep surgical site infection (Peto odds ratio = 7.08; 95% confidence interval: 1.39, 35.99; P = .02; I(2) = 0%), superficial surgical site infection, fixation failure, and reoperation to remove metalwork were more common after early ankle movement compared to immobilization. CONCLUSION: The quality of evidence is poor. The effects of early movement after ankle surgery on short-term functional outcomes are unclear, but there is no observable difference in the longer term. There is a small reduction in risk of postoperative thromboembolism with early ankle movement. Current evidence suggests that deep and superficial surgical site infections, fixation failure, and the need to remove metalwork are more common after early ankle movement. Level of Evidence Therapy, level 1a-.